Ingestion and Surgical Retrieval of an Endodontic File: A Case Report - Ptak, Devon M.; Alon, Elinor; Amato, Robert; Tassinari, Julia; Velasquez, Adrian (Journal of Case Reports in Dental Medicine, 2023)
Foreign body ingestions are rare, but do occasionally occur during dental treatment. It is estimated that the ingestion of endodontic instrument(s) occurs at an incidence of 0.12 per 100,000 root canal treatments.(1) Although reports of accidental foreign body ingestions exist, few have been able to follow the patients’ medical journey closely enough to capture photos demonstrating how extensive the surgical intervention necessary to manage such events may be. Perhaps this lack of visualization, and associated lack of awareness, is one of the reasons some clinicians still provide non-surgical root canal therapy (NSRCT) without a rubber dam. The case report outlines the medical treatment of a 30 year old male who ingested a K file during NSRCT. The patient was referred to a nearby hospital for subsequent evaluation and treatment, which consisted of numerous imaging studies, endoscopic evaluation, and surgical removal of the K file from his small intestine.